Development of the Institution of Arbitration in Kazakhstan: Problems of Theory and Practice - SHAIMENOVA, Ardak; ILYASSOVA, Gulzhazira; KLYUYEVA, Yevgeniya; KHASHIMOVA, Ainura (Journal of Advanced Research in Law and Economics, 2020)
The article discusses current issues of the application of the legislation of Kazakhstan on arbitration, provides statistical data on the results of consideration of cases on the cancellation of arbitral awards, on the enforcement of arbitral awards and identifies some problems of theory and practice in this area. The aim of the study is a comprehensive analysis of judicial practice on the abolition of arbitral awards, as well as issues related to their enforcement, proposals have been developed on the formation of a uniform judicial practice and improvement of legislation. The work uses general scientific and special research methods: analysis, synthesis, abstraction, induction, deduction, logical and comparative legal method. As a result of the study, the author came to the conclusion that, in general, the norms of the Law of Kazakhstan ‘On Arbitration’, the Civil Procedure Code of Kazakhstan on the procedures for canceling arbitration decisions, recognition and enforcement of decisions of foreign arbitrations are consistent with international treaties.